2015
DOI: 10.1016/j.toxrep.2015.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of changes in energy metabolism parameters provoked by carbon tetrachloride in Wistar rats and the protective effect of white grape juice

Abstract: The objective of this study was to evaluate the effect of organic and conventional grape juices consumption on the behavior of rats and their neuroprotective effect on the activity of brain energy metabolism enzymes in different brain areas of adult rats on the experimental model of hepatic encephalopathy. Male Wistar rats (90-days-old) were treated once a day with conventional or organic white grape juice by gavage for 14 days (7 μL/g). On the 15th day the rats received carbon tetrachloride (CCl4) in a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 69 publications
(79 reference statements)
1
6
1
Order By: Relevance
“…In our experiment, the animals treated with grape juice showed no significant difference between the groups. The same was found in other study of our group [33]. Our study is the first study to show this experimental design and this result.…”
Section: Resultssupporting
confidence: 90%
“…In our experiment, the animals treated with grape juice showed no significant difference between the groups. The same was found in other study of our group [33]. Our study is the first study to show this experimental design and this result.…”
Section: Resultssupporting
confidence: 90%
“…Rizzon and Miele [19] found values of 0.03 g/100g of acetic acid for whole juices, 0.05 g/100g of acetic acid for sweetened juices and 0.02 g/100g of acetic acid for the reprocessed juice, which are lower values than most found in this study. Gabardo et al [24] observed volatile acidity of 0.04 g/100g of acetic acid for both conventionally produced and organic white grape juice, those being low numbers when compared to the present work.…”
Section: Resultscontrasting
confidence: 69%
“…Canadian researchers [23] prepared juices from 10 different cultivars and found pH values of 2.38 to 3.13, displaying a lower number than the lowest observed in this study (2.81 for a white grape juice from the crop of 2013). Gabardo et al (2015) [24] evaluated the protective effect of white grape juice in rats and observed a pH of 3.89 in organic white grape juice and 3.58 in conventionally produced white grape juice, those being notably high values compared to the means of the present work.…”
Section: Resultsmentioning
confidence: 63%
“…In this context, polyphenol compounds found in grape juice have been associated with multiple health benefits including improvement in cognition and neuronal function with aging [21][22][23]. Experimental studies conducted by our research group demonstrated the neuroprotective effects of chronic purple grape juice consumption in several brain areas from rats submitted to different damage models [24][25][26].…”
Section: Introductionmentioning
confidence: 92%